Thermal action on normal and high strength cement mortars - Ripani, Marianela (2020)
High temperature effect on cement-based composites, such as concrete or mortars, represents one of the most important damaging process that may drastically affect the mechanical and durability characteristics of structures. In this paper, the results of an experimental campaign on cement mortars submitted to high temperatures are reported and discussed. Particularly, two mixtures (i.e., Normal (MNS) and High Strength Mortar (MHS)) having different water-to-binder ratios were designed and evaluated in order to investigate the incidence of both the mortar composition and the effects of thermal treatments on their physical and mechanical properties. Mortar specimens were thermally treated in an electrical furnace, being submitted to the action of temperatures ranging from 100 to 600 °C. After that and for each mortar quality and considered temperature, including the room temperature case of 20 °C, water absorption was measured by following a capillary water absorption test. Furthermore, uniaxial compression, splitting tensile and three-points bending tests were performed under residual conditions. A comparative analysis of the progressive damage caused by temperature on physical and mechanical properties of the considered mortars types is presented. On one hand, increasing temperatures produced increasing water absorption coefficients, evidencing the effect of thermal damages which may cause an increase in the mortars accessible porosity. However, under these circumstances, the internal porosity structure of lower w/b ratio mixtures results much more thermally-damaged than those of MNS. On the other hand, strengths suffered a progressive degradation due to temperature rises. While at low to medium temperatures, strength loss resulted similar for both mortar types, at higher temperature, MNS presented a relatively greater strength loss than that of MHS. The action of temperature also caused in all cases a decrease of Young's Modulus and an increase in the strain corresponding to peak load. However, MHS showed a much more brittle behavior in comparison with that of MNS, for all temperature cases. Finally, the obtained results demonstrated that mortar quality cannot be neglected when the action of temperature is considered, being the final material performance dependent on the physical properties which, in turn, mainly depend on the mixture proportioning.